The jet engine (Chichester, West Sussex ; Hoboken, NJ : John Wiley & Sons Inc., 2015)
'The Jet Engine provides a complete, accessible description of the working and underlying principles of the gas turbine. Written by Rolls-Royce gas turbine engineers, it contains a wealth of detail and high-quality illustrations'--
Includes bibliographical references and index.
Keywords: Airplanes -- Turbojet engines; Airplanes -- Jet propulsion